2011
DOI: 10.1248/yakushi.131.1629
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Symptoms, Adherence and Satisfaction after Pharmaceutical Care at Asthma Clinic for Outpatient

Abstract: In the present study, we investigated whether counseling at an outpatient asthma clinic improved asthma symptoms, adherence and patient satisfaction: The asthma control test (ACT) and asthma control questionnaire (ACQ) were used to assess subjective symptoms, 10-item version of the drug attitude inventory (DAI-10) was used to determine medication adherence, and 8-item Japanese version of the client satisfaction questionnaire (CSQ-8J) was used to ascertain patient satisfaction. All scores of inhalation techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…25 These seemingly negative results, however, do not exclude the need for a pharmacist to review respiratory patients in a specialist outpatient setting as pharmacists are well placed to provide counselling. In an asthma clinic in Japan, 26 pharmacist counselling improved asthma symptoms, adherence and patient satisfaction. Furthermore, pharmacists have the opportunity to identify both The impact of a clinical pharmacist in a thoracic outpatient clinic respiratory and non-respiratory DRPs.…”
Section: Discussionmentioning
confidence: 99%
“…25 These seemingly negative results, however, do not exclude the need for a pharmacist to review respiratory patients in a specialist outpatient setting as pharmacists are well placed to provide counselling. In an asthma clinic in Japan, 26 pharmacist counselling improved asthma symptoms, adherence and patient satisfaction. Furthermore, pharmacists have the opportunity to identify both The impact of a clinical pharmacist in a thoracic outpatient clinic respiratory and non-respiratory DRPs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, repeated counseling in the PMC improved PEFR and maintained it at a high level for over 2 years [ 40 ]. Subsequent studies demonstrated that pharmaceutical education and counseling in the PMC for asthma were effective in enhancing patients’ knowledge and adherence and increasing the PEFR of patients with any disease severity from mild to severe [ 69 , 70 ]. Significant positive correlations of medication adherence with inhalation technique and insights into the disease and medication were observed, but not with the state of disease control.…”
Section: Reviewmentioning
confidence: 99%